Effectiveness of The Regional Revenue Agency Organization of Bekasi District in Optimizing Rural and Urban Land and Building Tax (PBB-P2) to Increase PAD - Vega Megiantary; Heru Nurasa; Sawitri Budi Utami (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study analyzes the effectiveness of the Bekasi Regency Regional Revenue Agency (Bapenda) organization in optimizing Rural and Urban Land and Building Tax (PBB-P2) to increase Regional Original Income (PAD). Organizational effectiveness is measured through five main aspects, namely production, efficiency, satisfaction, adaptation, and organizational development. The research method used is a qualitative approach with in-depth interviews with stakeholders, including structural officials at Bapenda, field officers, and PBB-P2 taxpayers. The results of the study indicate that production effectiveness depends on strategic planning, tax data accuracy, and increased taxpayer compliance. Efficiency in tax collection can be improved through digitalization of the administration system and optimization of human resources. Taxpayer satisfaction is influenced by the quality of service, transparency of information, and ease of access to tax services. The organization's ability to adapt to changes in policy, technology, and socio-economic conditions is an important factor in maintaining the stability of tax revenues. In addition, organizational development through innovation, employee training, and collaboration with various stakeholders is a strategic step in increasing the effectiveness of PBB-P2 collection. Therefore, increasing the effectiveness of the Bekasi Regency Bapenda organization needs to be continuously carried out through strengthening governance, more optimal use of technology, and improving the quality of services to the community to support sustainable increases in PAD.